The Influence Of Agile Leadership, Innovative Work Behavior And Organizational Commitment Through Work Productivity On Institutional Performance In The Industrial Era 4.0 (Case Study At Lp3i Jakarta Polytechnic) - Jaenudin Akhmad; Arisseyanto Nugroho; Darmansyah (ASIAN PUBLISHER, 2024)
Digital revolution and the era of technological disruption are other terms for industry 4.0. One of the unique characteristics of industry 4.0 is the application of artificial intelligence (Tjandrawinata, 2016). Agile leadership is a leadership style that is much needed in this modern era. Technological disruption, global economic turmoil, and climate change, make the challenges of the current era increasingly complex. Innovative Work Behavior describes the behavior of a series of employee activities that implement and conduct exploration in the Company in order to improve the performance of employees and the company where they work. Organizational commitment is also an important factor in organizations. Organizational commitment is a condition of employees who side with the organization with goals that are in accordance with the organization's vision and mission and continue to remain as employees in the company. The population of this research are leaders in the Structural Directorate and Campus of the LP3I Jakarta Polytechnic. This research sample has 5 (five) variables and has 21 indicators, so based on the opinion (Hair et al, 2014) above, a sample of 7 x 21 or the same as 147 is needed, so based on the calculation above the number of samples that will be taken is 147 respondents. The data analysis technique uses SEM-Partial Least Square (PLS). The results of this research show that Agile Leadership, Innovative Work Behavior, Organizational Commitment have a significant influence on the Performance of the LP3I Jakarta Polytechnic Institution. The Agile Leadership variable has a significant effect on the Performance of the LP3I Jakarta Polytechnic Institution through Work Productivity; Innovative Work Behavior has a significant effect on the Performance of the LP3I Jakarta Polytechnic Institution through Work Productivity; Organizational Commitment has a significant influence on the Performance of the LP3I Jakarta Polytechnic Institution through Work Productivity.